Collahuasi paste thickener — pilot and full-scale results - Loan, C.; Villanueva, M.L.; Saldia, N. (Paste 2011: Proceedings of the 14th International Seminar on Paste and Thickened Tailings, 2011)
The ever increasing scarcity of water has driven many operators to consider paste thickening as a viable means of disposal, maximising water conservation by increasing underflow density of traditional tailings. Being located in arguably the driest place on earth makes water conservation a top priority for Collahuasi and is a major constraint for organic growth in copper production. As such Collahuasi and Outotec have invested considerable resources into piloting, designing and operating a full-scale demonstration paste thickener at Collahuasi’s operations. This paper addresses the critical stages in piloting and size determination along with full-scale operational results post installation.